Antibacterial of Cinnamon Bark (Cinnamomum burmannii) Essential Oil Against Methicillin-Resistant Staphylococcus aureus - Fadlilah, Shinta Levea Ni'matul; Effendi, Mustofa Helmi; Tyasningsih, Wiwiek; Suwanti, Lucia Tri; Rahmahani, Jola; Harijani, Nenny; Ramandinianto, Sancaka Chasyer; Khairullah, Aswin Rafif (Universitas Airlangga, 2021)
This study aimed to determine the in vitro antibacterial activities of essential oil from cinnamon bark (Cinnamomum burmannii) on Methicillin-resistant Staphylococcus aureus (MRSA) isolated from raw milk. Essential oil from cinnamon bark obtained from the steam distillation method and essential oil was made in a series dilution with a concentration of 1%, 2%, 4%, and 8%. The antibacterial activities were tested using the disk diffusion method. Results showed from five isolates of MRSA, one isolate was sensitive of essential oil with a concentration 2% and all of the isolate was sensitive with a concentration 4% and 8%. The antibacterial activity showed by inhibition zones on MRSA. The results suggest that the activity of the essential oils of cinnamon bark has an antibacterial effect on MRSA and it is developed as phytopharmaca.